PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI FINANSIAL TIDAK LANGSUNG TERHADAP KINERJA KARYAWAN PADA PT. POS INDONESIA CABANG KUPANG - Christin Dwi Cahyani Rini; Leony M Ndoen; Struce Andriyani (Journal of Management Small and Medium Enterprises (SMEs), 2019)
This research was conducted at PT. Pos Indonesia Kupang Branch. The problem in this research is, "Does the organizational culture affect the performance of employees at PT. Pos Indonesia Kupang Branch "," Does financial compensation indirectly affect the performance of employees at PT. Pos Indonesia Branch Kupang ", and" Does the organizational culture and financial compensation indirectly simultaneously affect the performance of employees at PT. Pos Indonesia Kupang Branch? ". The results of the research show that the Organizational Culture owned by employees of PT. Pos Indonesia Kupang Branch, which consists of 7 (seven) indicators, namely adaptability, autonomy, cooperation, creativity, equality, honesty, rationality has a positive influence on the performance of employees at PT. Pos Indonesia Kupang Branch. Indirect financial compensation owned by employees of PT. Pos Indoensia Kupang Branch, which consists of 3 (three) indicators, namely security and welfare, payment of wages for not working, and services for workers have a positive influence on the performance of employees at PT. Pos Indonesia Kupang Branch. Thus, the company needs to maintain and improve the organizational culture and financial compensation is not directly appropriate so that employee performance will increase. When employee performance increases, the organization can achieve its goals and objectives well. Keywords: organizational culture, indirect financial compensation, and employee performance